Explaining penny stock returns versus non-penny stock returns from a liquidity perspective - Syed Sallehuddin, Sharifah Nadhira; Che-Yahya, Norliza; Soo, Cheng Chuah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
The presence of higher penny stock returns in the Malaysian stock market in recent years may have attracted the attention of investors. On the other hand, it indicates a liquidity risk premium, implying a higher risk associated with the stocks. Employing yearly panel data of 434 penny firms and 319 non-penny firms from 1st January 2019 to 31st December 2023, this study aimed to explain penny stock returns versus non-penny stock returns in the Malaysian stock market from a liquidity perspective. The dependent variables were penny and non-penny stock returns in the Malaysian stock market meanwhile, the main independent variable was liquidity. The other independent variables consisted of the factors in the five-factor model; risk, firm size, book-to-market, and momentum. Further, this study employed three static panel data, namely Pooled Ordinary Least Squares, Random Effects Model and Fixed Effects Model. The finding showed that liquidity, book-to-market, and momentum influenced penny stock returns significantly. Simultaneously, liquidity, firm size, and momentum influenced non-penny stock returns in the Malaysian stock market.